2013
DOI: 10.1002/jsfa.6330
|View full text |Cite
|
Sign up to set email alerts
|

Aroma‐active components of yeast extract pastes with a basic and characteristic meaty flavour

Abstract: The key aroma-active compounds were identified in basic and characteristic meaty flavour yeast extract pastes, and their characterisation was determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 14 publications
1
48
0
Order By: Relevance
“…In addition, it has been reported that the combination of benzyl alcohol, 1-octen-3-ol and 2-octen-1-ol imparts a heavy, plant-like odor to enzymatic hydrolysates (Josephson et al, 1984a). Among the aldehydes, 2,4-heptadienal and (Chung et al, 2001;Chung et al, 2002;Lin et al, 2014) Note: '--' indicates that the corresponding compound was not detected. 2,4-decadienal, which are formed from the autoxidation of unsaturated fatty acids, have been identified as common odor compounds in aquatic products (Duflos, et al, 2006;Iglesias and Medina, 2008).…”
Section: Spme-gc-ms Analysismentioning
confidence: 99%
“…In addition, it has been reported that the combination of benzyl alcohol, 1-octen-3-ol and 2-octen-1-ol imparts a heavy, plant-like odor to enzymatic hydrolysates (Josephson et al, 1984a). Among the aldehydes, 2,4-heptadienal and (Chung et al, 2001;Chung et al, 2002;Lin et al, 2014) Note: '--' indicates that the corresponding compound was not detected. 2,4-decadienal, which are formed from the autoxidation of unsaturated fatty acids, have been identified as common odor compounds in aquatic products (Duflos, et al, 2006;Iglesias and Medina, 2008).…”
Section: Spme-gc-ms Analysismentioning
confidence: 99%
“…As an important savory ingredient, yeast extract is also a rich source of flavor compounds or precursors such as amino acids, peptides, sugars, nucleotides and B group vitamins . In the past decades, some studies were performed on the identification of aroma‐active compounds in yeast extract . Umami substances in yeast extract were also investigated, and l ‐glutamic acid, l ‐aspartic acid, succinic acid, inosine 5′‐monophosphate and guanosine 5′‐monophosphate were recognized .…”
Section: Introductionmentioning
confidence: 99%
“…The semi quantification method was adopted from our previously established experimental protocol (Alim et al., ). The compounds selection was done tentatively through calculating its retention index, mass spectrum, odor description, and with IS methodology (Lin et al., ). The concentrations of all reported volatile compounds were calculated through semi quantification technique Table .…”
Section: Resultsmentioning
confidence: 99%
“…(Lin et al., ) reported 10 pyrazines in yeast extract pastes extracted from dynamic head space (DHS) and simultaneous distillation extraction by thermal trapping at 280 °C and 135 °C, respectively. These pyrazines were responsible in delivering a number of significant flavor notes including burnt, nutty, fried, roasted and meaty perceptions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation